How Do Sectoral FDIs Impact Income Disparities? An Analysis in the Emerging Markets - Wahyudin, Iyud`; Nachrowi, Nachrowi Djalal (International Journal of Economics and Financial Issues, 2018)
Foreign direct investments (FDIs) are an important determinant in the economic growth of a country. However, FDIs not only impact economic growth but also give side effects on income disparities. Further, the FDIs impacts on disparities depend on what sectors such FDIs are invested. This study analyzes how the FDIs impacts on the sectoral economies (primary and non-primary) of the income disparities in the emerging markets in 17 countries using the panel data from the period from 2003 until 2012. The results of the study indicated that the sectoral FDIs impact income disparities. Primary sector FDIs improve disparities of the countries that have low per capita but worsen the income disparities of the countries that have high per capita GDP, whereas the non-primary sector FDIs improve income disparities of the countries that have high per capita but worsen income disparity in the countries that have low per capita GDP. Keywords: income disparity, primary and non-primary sector FDI, emerging markets JEL Classifications: O15, O11, F21